Meta‐analysis: risk of hepatitis C virus infection associated with hospital‐based invasive procedures. Issue 4 (27th June 2022) - Henriot, Paul; Castry, Mathieu; Luong Nguyen, Liem Binh; Shimakawa, Yusuke; Jean, Kévin; Temime, Laura
Summary: Background: Healthcare settings, where invasive procedures are frequently performed, may play an important role in the transmission dynamics of blood‐borne pathogens when compliance with infection control precautions is suboptimal. Aims: To understand and quantify the role of hospital‐based invasive procedures on hepatitis C virus (HCV) transmission. Methods: We conducted a systematic review and meta‐analysis to identify recent studies reporting association measures of HCV infection risk that are linked to iatrogenic procedures. Based on expert opinion, invasive procedures were categorised into 10 groups for which pooled measures were calculated. Finally, the relationship between pooled measures and the country‐level HCV prevalence or the Healthcare Access and Quality (HAQ) index was assessed by meta‐regression. Results: We included 71 studies in the analysis. The most frequently evaluated procedures were blood transfusion (66 measures) and surgery (43 measures). The pooled odds ratio (OR) of HCV infection varied widely, ranging from 1.46 (95% confidence interval: 1.14–1.88) for dental procedures to 3.22 (1.7–6.11) for transplantation. The OR for blood transfusion was higher for transfusions performed before 1998 (3.77, 2.42–5.88) than for those without a specified/recent date (2.20, 1.77–2.75). In procedure‐specific analyses, the HCV infection risk was significantly negatively associated with the HAQ for endoscopy and positively associated with HCV prevalence for endoscopy and surgery. Conclusions: Various invasive procedures were significantly associated with HCV infection. Our results provide a ranking of procedures in terms of HCV risk that may be used for prioritisation of infection control interventions, especially in high HCV prevalence settings. Abstract : Association between HCV infection and 10 groups of hospital‐based procedures was investigated. This metaanalysis shows that healthcare settings remain a gateway of HCV infection; the provided ranking of procedures could be used to improve infection control interventions.